Factors influencing students’ employability skills in Pahang / Mohd Zaidi Mat Saat …[et al.] - Mat Saat, Mohd Zaidi; Saripin, Muhammed Soffiq; Musa, Noor Dalila; Ridzuan, Arifi (Universiti Teknologi MARA Cawangan Pahang, 2021)
Business management programmes are critical in developing highly competent workers to meet the demands of today's business environment. An empirical analysis of a business management programme is required to determine the effectiveness of programme courses in providing students with soft skills that will enable them to meet contemporary employment needs and professional expectations. This paper aims to assess factors that influence employability skills. A total of 91 students participated in this research. The result of PLS-SEM indicates reliability and personal presentation are significant determinants of employability skills, but honesty and enthusiasm were not significant factors. Thus, this study is essential to spur more significant improvement to produce high-quality graduates, and the findings could be used as a strategy to improve curriculum design.